2021
DOI: 10.35993/ijitl.v7i1.1507
|View full text |Cite
|
Sign up to set email alerts
|

ICT Professional Development Workshops and Classroom Implementation Challenges: Perceptions of Secondary School Teachers in Trinidad and Tobago

Abstract: The Ministry of Education (MoE) of The Republic of Trinidad and Tobago has recently embarked on another teacher training program to equip secondary school teachers with the necessary competencies for ICT infusion in their physical classrooms. This study aims to investigate the impact and usefulness of that program, and challenges that the teachers have been facing in its implementation. Thirteen interviews (eight one-on-one and five focused group) were conducted from forty trained teachers. The findings showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Implementing ICToriented SBTPD within the framework of ALT could be hampered by challenges such as the frequency of professional development programmes for teachers, incongruency between training contents and teachers' needs, insufficient ICT resources and infrastructure, as well as concerns over safety and protection of ICT equipment in schools (Ajani, 2021;Castro-Guzmán, 2021;Çelen & Seferoglu, 2020;Munje & Jita, 2020). To overcome these challenges, experts recommend exposing teachers to frequent ICT-oriented SBTPD that focuses on addressing their diverse classroom needs (Warner et al, 2021). Furthermore, the structuring of professional development programmes should adhere to criteria including needs-based content, active learning, duration, joint participation, compliance with individual needs, colleague collaboration, and expert support.…”
Section: Intrinsic-motivation Principle As Correlate Of Ict Training ...mentioning
confidence: 99%
“…Implementing ICToriented SBTPD within the framework of ALT could be hampered by challenges such as the frequency of professional development programmes for teachers, incongruency between training contents and teachers' needs, insufficient ICT resources and infrastructure, as well as concerns over safety and protection of ICT equipment in schools (Ajani, 2021;Castro-Guzmán, 2021;Çelen & Seferoglu, 2020;Munje & Jita, 2020). To overcome these challenges, experts recommend exposing teachers to frequent ICT-oriented SBTPD that focuses on addressing their diverse classroom needs (Warner et al, 2021). Furthermore, the structuring of professional development programmes should adhere to criteria including needs-based content, active learning, duration, joint participation, compliance with individual needs, colleague collaboration, and expert support.…”
Section: Intrinsic-motivation Principle As Correlate Of Ict Training ...mentioning
confidence: 99%
“…Online and digital technologies are evolving around the world rapidly. In the current era of globalization, online and digital technologies have been able to play a vital role in every field of life including the teaching-learning process (Malik, Azmat, & Bashir, 2020;Warner, Malik, & Mohammed, 2021). The distance learning paradigm opened up doors for even more technologies.…”
Section: Blended Learning Its Roles and Importancementioning
confidence: 99%
“…Before the pandemic, elementary schools in Trinidad and Tobago were not equipped with an abundance of trained teachers to infuse technology in teaching and learning neither was there sufficient hardware and software, and infrastructure to deliver teaching and learning using technology (Johnson et al, 2016;MoE, 2017;Warner, Malik & Mohammed, 2021). There exist many challenges and several external factors to teachers such as who will provide continuous professional development training and support to elementary school teachers and maintenance of existing technology resources (Warner, Malik & Mohammed, 2021). This suggested that if teachers had some vital training to infuse technology in their teaching and learning, the transition could have been fraught with less pedagogical challenges.…”
Section: Introductionmentioning
confidence: 99%